Free-standing electrochemically coated MoSx based 3D-printed nanocarbon electrode for solid-state supercapacitor application - Ghosh, Kalyan; Pumera, Martin (Nanoscale, 2021)
The 3D-printing technology offers an innovative approach to develop energy storage devices because of its ability to create facile and low cost customized electrodes for modern electronics. Among the recently explored 2D nanomaterials beyond graphene, molybdenum sulfide (MoSx) has been found as a promising material for electrochemical energy storage devices. In this study, a nanocarbon-based conductive filament was 3D-printed and then activated by solvent treatment, followed by electrodeposition of MoSx on the printed nanocarbon electrode's surface. The conductive nanocarbon fibers allow a coaxial deposition of a thin MoSx layer. The MoSx layer contributes to pseudocapacitive charge storage mechanisms to obtain higher capacitances. In a three-electrode test system with 1 M H2SO4 as electrolyte, the MoSx coated 3D-printed electrode (MoSx@3D-PE) electrode shows a capacitance of 27 mF cm-2 at the scan rate of 10 mV s-1, and a capacitance of 11.6 mF cm-2 at the current density of 0.13 mA cm-2. Extending to solid-state supercapacitor (SS-SC), the cells were fabricated using the MoSx@3D-PE with different designs and polyvinyl alcohol (PVA)/H2SO4 as gel electrolyte. An interdigital-shaped SS-SC provided a specific capacitance of 4.15 mF cm-2 at a current density of 0.05 mA cm-2. Moreover, it showed a stable cycle life where 10% capacitance loss was found after 10 000 cycles. Briefly, this study reports the integration of 3D-printing and room-temperature electrodeposition techniques allowing a simple way of fabricating customized free-standing 3D-electrodes for use in SC applications.